(untitled) (Research, Society and Development, 2022)
Introduction: Bulk fill resins emerged from the search for an aesthetic material with favorable biomechanical properties and simplified technique, becoming a strategy for restorative procedures in public health. However, its clinical applicability still causes uncertainties for professionals. The present study aims to analyze, through literature review, characteristics, properties, and clinical applicability of bulk fill resins. Methods: Bibliographic study, with a qualitative approach, of the critical literature review type, carried out in PubMed/MEDLINE, Scopus, Google Scholar and SciELO databases, selecting articles from laboratory and clinical studies from 2015 to 2020. Results: In vitro studies and randomized clinical trials demonstrate that bulk fill resins of regular consistency have shown mechanical properties similar to conventional resins. Bulk fill resins, in different viscosity grades, can save time, with a simplified technique and obtain satisfactory results. It is suggested that the use of these resins in extensive reconstructions, events which require agility, such as care for children and people with disabilities, including in the public service, as an alternative to cases in which amalgam or glass ionomer cement would be used as a restorative material. However, currently the high cost and greater translucency of some resins giving a grayish appearance to restorations to anterior teeth, are some factors that contraindicate their use. Conclusion: Bulk fill resins are a suitable material for direct restorations in posterior teeth, mainly due to the simplification of the technique, making it possible to optimize aesthetic procedures that require more clinical time, without compromising the quality of the treatment.